UNDISAN TOURISM VILLAGE IN BANGLI EAST OF BALI, IS A GREEN TOURISM WHERE THE TOURISTS CAN COOK A BALINESE CULINAIR TO MAINTAIN SUSTAINABLE TOURISM - I Wayan Pugra (Journal of Business on Hospitality and Tourism, 2016)
Nowadays the Balinese culinair is getting famous in all over Bali which are consumed by Balinese TouristsBalinese food is available in local restaurant and international restaurant too in Bali.Miss Rebecca Gilling who found the Denpasar Moon song, about four years ago was loving Jukut Ares (vegetable, is made from young banana tree).Balinese food are available in big event such as in seminar, in wedding ceremony, birthday party and in international event.Nowadays many tourists want to taste a different food to prevent boaring but want to experiencing a unique taste of Balinese cuisines.Mr. Patrice, an owner of a travel agent in French has a smart idea to bring his tourist to visit the Undisan Tourism Village, in Bangli, in east part of Bali, to enjoy the beautiful panorama of Bali, while learning the local culture of Bali. Here in Undisan Tourism Village, the tourist can practice cooking Balinese traditional food, one among them is Sate Lilit.This activity is the best way and the best idea to apply The Green Tourism to maintain the sustainable  tourism, especially in Bali.